Increasing jute (Corchorus olitorius L.) fiber yield through hybridization and combining ability studies to break the yield plateau - Chourasia, Kumar Nishant; Meena, Jitendra Kumar; Bhowmick, Rakesh; Mangal, Vikas; Arroju, Anil Kumar; R, Thribhuvan; Kar, Chandan Sourav; Bera, Amit; Satya, Pratik; Mitra, Jiban; Kar, Gouranga (Frontiers in Plant Science, 2025)
The growing global demand and shift from synthetic to natural fibers highlight the need to overcome the yield plateau in jute production. Despite being a sustainable alternative to plastic, jute faces declining cultivation, making yield improvement crucial to meet increasing demand. In this direction, the study was designed to explore hybridization and combining ability to improve the genetic yield potential of jute. Using a diallel mating design, 90 hybrid combinations were evaluated along with 10 parental lines, focusing on traits such as fiber yield, plant height, basal diameter, stick weight, and green biomass. The investigation revealed JROBA 3 and JBO 1 as the most effective general combiners, highlighting their significant potential as parents to produce outstanding hybrids and generate good transgressive segregants. Among the tested hybrids, JROBA 3 × JRO 2407 was found to have very high specific combining ability (SCA), yielding 24.42% more than the national check variety, JRO 204. A correlation study was also conducted, revealing that stick weight had a strong positive correlation with fiber yield, highlighting it as a key factor in selecting high-yielding hybrids. This study also identified the hybrid JROBA 3 x JBO 1 which exhibited an 18% biomass yield advantage over the national check variety. Positive mid-parent heterosis and better-parent heterosis were observed in hybrids, further demonstrating the effectiveness of hybridization in jute breeding. Parent genetic diversity was characterized using intron-length polymorphism markers. Molecular diversity analysis categorized the varieties into two distinct clusters, suggesting possible avenues for integrating improved features into future jute types. This study has established the fact that heterosis breeding can efficiently improve fiber productivity through the involvement of non-additive gene action. The application of heterosis breeding to improve jute production presents a significant opportunity for breeders, aligning well with sustainable development goals and promoting the use of biodegradable fiber alternatives.